Mechanism of Core Browning in Different Maturity Stages of ‘Yali’ Pears During Slow-Cooling Storage and PbRAV-Mediated Regulation - Bing Deng; Qingxiu Li; Liya Liang; Hongyan Zhang; Xiaoyu Zhang (Foods)
This study investigated the impact of slow cooling on browning and fruit quality at three maturity stages (early, mid and late). Slow cooling reduced core browning in early/mid-harvest pears, as the browning indexes of early-, middle- and late-harvested ‘Yali’ pears at 60 d were 0.13, 0 and 0.1, respectively, preserving firmness and soluble solids. Transcriptomic analysis revealed that upregulated genes in ‘Yali’ pears facilitated stress adaptation via enhanced catalytic activity and phosphorylation. Mid-harvested pears exhibited activation of phosphorus metabolism and DNA repair mechanisms to maintain cellular homeostasis, whereas the late-harvested counterparts showed significant suppression of photosynthesis-related pathways and pyrimidine metabolism, which collectively accelerated senescence progression. Universal downregulation of hormone-response pathways such as ethylene and auxin revealed systemic stress adaptation decline. Then, the PbRAV transcription factors’ role was also studied. EMSA confirmed that GST-PbRAV2 binds to the PbLAC15 promoter, linking RAV2 to laccase regulation. Overripe pears showed PbRAV2 dysregulation, impairing LAC15 suppression and accelerating browning. Findings provide a theoretical basis for using slow cooling to mitigate browning in pear storage.